FRI0487 Cardiac Magnetic Resonance in the Evaluation of Symptomatic Patients with Systemic Sclerosis: Correlation with Clinical Characteristics and Arrhythmic Burden. (9th June 2015) - Bosello, S.; De Luca, G.; Meduri, A.; Berardi, G.; Rucco, M.; Canestrari, G.; Parisi, F.; Silvestri, V.; Marano, R.; Bonomo, L.; Ferraccioli, G.
Abstract : Background: Cardiovascular magnetic resonance imaging (CMRI) has been proposed as a useful tool for early assessment of sub-clinical cardiac involvement in Systemic Sclerosis (SSc). Objectives: To evaluate the role of CMRI in the detection of cardiac involvement in selected SSc patients. Methods: Fifty SSc-patients with symptoms of cardiac involvement (dyspnea, palpitations) and/or elevation of cardiac troponin T underwent CMRI. Twenty sex and aged matched healthy controls were also enrolled. Clinical and cardiac (echocardiography and 24h-ECG-Holter) characteristics were available for all scleroderma patients. Results: SSc patients and healthy controls presented comparable end-diastolic volume (EDV) and end-systolic volume (ESV) of right and left ventricles. Despite SSc patients presented lower left ventricle ejection fraction (EF)(61.2±10.8%) and lower right ventricle EF (57.5±12.2%) compared to healthy controls (LVEF:64.3±4.9% and RVEF:61.2±3.6%), the differences were not statistically significant. Nineteen SSc patients (38%) presented abnormalities on CMRI study, with respect to none of the healthy controls. CMRI demonstrated T2 hyperintensity in 5 SSc patients (10%), while none of the patients presented early gadolinium enhancement and 17 (34%) patients presented late gadolinium enhancement (LGE). We identified 3 different patterns of distribution of LGE: subepicardial, midwall and subendocardial. Fourteen patients (82.3%) presented a single pattern of distribution, while 3 patients (17.7%) presented more than one: 58.8% of patients presented a midwall distribution of LGE, 29.4% of patients presented a subepicardial LGE with a linear distribution pattern and 35.3% presented a subendocardial LGE distribution. Twelve SSc patients (38%) showed hypokinetic area and only one patient an akinetic area. Twenty-two SSc patients (44.0%) presented a pericardial effusion on CMRI. Patients with CMRI abnormalities presented a longer disease duration (10.1±5.6 years) when compared with SSc patients without CMRI abnormalities (4.3±7.6 years, p=0.003). Furthermore, LVEF and RVEF were lower in patients with CMRI abnormalities, while ESV of both ventricles was higher in these SSc patients when compared to SSc patients with normal CMRI. Finally, in SSc patients LVEF inversely correlated with disease duration (R=-0.3, p=0.035) and number of ventricular ectopic beats (VEBs) on 24h-ECG Holter (R=-0.3, p=0.04). Interestingly, considering the right ventricle, the number of VEBs inversely correlated also with EF (R=-0.4, p=0.04) and directly correlated with EDV (R=0.4, p=0.01) and ESV (R=0.5, p=0.002). Conclusions: CMRI could be a useful tool to detect abnormal ventricular function and volumes and allows to identify cardiac abnormalities (T2 hyperintensity and LGE) in a subgroup of scleroderma patients. Even though the correlations between EF, end-systolic and diastolic volumes of both ventricles and some clinical characteristics (disease duration and number of VEBs) suggest a possible clinical significance of CMRI abnormalities, their real clinical value need to be further investigated. Disclosure of Interest: None declared